Measuring noise and vibration in the cockpit of the Mi-8 helicopter - Stojanović, Ivica S. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Noise and vibration are among the main negative elements of the working environment. The aim of this study was to determine the measurement of the size of their effect on helicopter pilots and crew members. The results were compared with the warning and limit values ​​determined by the existing Directives of the European Commission in the field of noise and vibration. The comparison of the results has led to the conclusion that the measured values ​​are unacceptable in terms of safety and health at work and that the measured values ​​exceed the limits. The measurements have pointed out to a danger of occupational diseases among crew members and to the necessity to take measures to reduce the harmful effects of noise and vibration on helicopter personnel. Introduction Noise and vibration are by nature an integral part of everyday life and a part of the human environment. They appear as a companion to life’s many activities and their presence is evident in almost all spheres. The subject of this study was to assess the level of noise and vibration generated in the cockpit of the Mi-8 affecting the crew. The aim of the research was to obtain results that will show whether noise and vibration in the helicopter cockpit exceed allowable limits set by standards, to support the final analysis with measurement results and to illustrate a detrimental effect of noise and vibration on the human body. The Mi-8 helicopter was selected for measurements. Noise and vibration were measured in the cockpit of the helicopter so as to find out whether the helicopter engine compartment is a source of the negative impact of noise and vibration on pilots and how significant this negative impact is. In order to implement the basic procedures of noise control, assess the state of the noise level and the noise harmful effects on the human body as well as to apply the most appropriate method for noise reduction, it is necessary to have as complete and accurate information on the noise characteristics as possible, which can be determined by measuring the noise characteristic values in the amplitude, frequency and time domains. Measurements are necessary to determine the three basic characteristics of noise: strength, frequency and duration. The above three parameters completely describe the character of noise. Regarding vibrations, there are three categories of vibrations people are exposed to. These are: self-excited (coming from every-day movements such as walking, running or recreation), forced vibrations during psycho-physiological involvement (vibrations to which operators, including pilots, are exposed) and forced vibrations without psycho-physiological involvement (vibrations to which people are exposed regardless of their will, e.g. in transportation vehicles, offices, apartments, etc.). In addition to assessing harmful effects on the health and safety of people, vibration measurements can be used as a diagnostic tool. Vibration measurements can lead to a significantly faster inspection of failures and to the prevention from catastrophic consequences for personnel and technical equipment. The current practice requires a control of the functioning of helicopter parts as well as their replacement after the prescribed time or exploitation periods. This makes helicopter maintenance procedures expensive. The solution to this problem is the development of the Health and Usage Monitoring Systems – HUMS, used for detecting initial failures in parts of the helicopter, for predicting remaining service life and for creating conditions for the transition from preventive-based maintenance to condition-based maintenance. The effect of noise on the human body The impacts of noise on humans are divided into physiological and psychological ones. Physiological effects, both auditory and nonauditory, cause changes in physiological mechanisms or functions related to noise. Auditory effects have a direct impact on the peripheral auditory system and the hearing as a whole. Exposure to the acoustic energy may cause certain nonauditory effects, such as effects on the vestibular system and the autonomous nervous system, causing sleep disturbance, fatigue and stress. However, these nonauditory effects, except for a few exceptions, are also transmitted through the auditory system. Not only does noise threaten the health of helicopter crew, but also affects the quality of communication between crew members. Noise represents a potential threat to the safety and operation of the aircraft, reducing the effectiveness and efficiency of communication, as well as preventing the alarms and other warning messages to be timely and accurately heard and received. The effect of vibrations on the human body Helicopter pilots are exposed to whole-body vibrations in the working environment. Pain in the lower back is associated with whole-body vibrations and pilots can be said to have more trouble with this kind of pain compared to other professions. Helicopters have several major sources of vibration, such as the main rotor, the tail rotor and the engine. These vibrations are transmitted to the crew through all contact surfaces, including the floor, control equipment and seats. Realization of noise and vibration measurements Noise and vibration measurements were performed on the Mi-8 helicopter of the Army of Serbia. All measurements were performed in the helicopter cockpit in four phases of flight: -during standing, before takeoff, -during a preparation for takeoff, -during flight, and -during landing. Vibration measurements The results of measurements point out to the following: - The value of A (8) is higher than the value of the action value and limit values set in Directive 2002/44 / EC; - It only takes 2 seconds to reach the action value, and only 12 seconds for the marginal value of vibration; - The maximum vibration value is in the direction of the z-axis; - Diagrams identify four phases of flight (engine start-up, acceleration of rotation before takeoff, flight and landing and stationary work). The figure shows that, even at the stage before takeoff, vibrations are above the action value, and in the phase of flight they are far above the limit value; - Bearing in mind the recommendations of Directive 2002/44 / EC, it is clear that certain measures have to be taken to reduce the harmful effects of vibration on the health and safety of people. Noise measurements The results of measurements indicate the following: - the value of LEX,8h exceeds the exposure limit values ​​(87 dB) required by Directive 2003/10/CE; - Bearing in mind the recommendations of Directive 2003/10/CE, it is clear that certain measures have to be taken to reduce the harmful effects of noise on health and safety of people. Conclusion The aim of this study was to determine the levels of noise and vibration in the helicopter cockpit and to compare the obtained results with the action and limit values required by the relevant directives of the European Commission relating to noise and vibration. Measurements and comparisons of the results has led to the conclusion that in the helicopter cockpit noise and vibration values ​​exceed the limit values ​​set by Directives 2003/10 / CE for noise and 2002/44 / EC for vibration. Due to harmful effects of noise and vibration on human health, some of which were highlighted in this paper, there is a need for: - periodic measurements of noise and vibration in helicopters, - periodic monitoring of the health status of helicopter crews, especially specialist medical check-ups of potentially most vulnerable organs exposed to the effects of noise and vibration, - activating the available technical capacity of the Army of Serbia with the help of professional institutions of civil structures to find ways to reduce noise and vibration at their sources as well as along their transmission paths. In the literature and in practice there are a number of ways of mitigating the harmful effects of noise and vibration on the human body and it is necessary to apply the experience of experts on the helicopters of the Army of Serbia, - taking technical, organizational, regulatory, educational and other measures to reduce personnel exposure to harmful effects of noise and vibration. This work should serve not as a definitive conclusion about the quality of the working environment in the Mi-8 helicopter, but as a basis for further research that would aim at discovering the causes of noise and vibration and their transmission paths to the helicopter cockpit, in order to find methods of their reduction.